Cardioversion Of Atrial Fibrillation And Oral Anticoagulation - Airaksinen, KE Juhani (J Atr Fibrillation, 2015)
The risk of thromboembolic events is a major concern in cardioversion of atrial fibrillation. The vast majority of these events occur in the first week following cardioversion. Processes promoting thrombus formation occur early and thrombus may appear in the left atrium within 48 hours of atrial fibrillation. The risk of thromboembolic events also increases with the presence of stroke risk factors. Thus, the current guidelines recommend that also patients with acute atrial fibrillation should undergo cardioversion under cover of unfractionated or low-molecular weight heparin followed by oral anticoagulation for at least 4 weeks in patients at moderate-to-high risk for stroke. Delay of cardioversion < 12 hours from the symptom onset seems to cause a marked increase in the risk of stroke. Thus, short term anticoagulation should be considered also for patients with a low CHA(2)DS(2)VASc score if the delay to cardioversion is 12-48 hours.